Urban Renewal and the End of Social Housing: The Roll Out of Neoliberalism in East Berlin's Prenzlauer Berg - Holm, Andrej (Social justice, 2006)
Part of a special issue on resistance to neoliberal globalization. The present stage of urban renewal marks a passage into a neoliberal strategy that replaces the prior orientation toward welfare. The phase is characterized by a new type of urban governance, with a stronger involvement of private investors and interests in urban development. This neoliberal turn of urban policy is typified by the renewal of the district known as Prenzlauer Berg in Berlin. The experience of urban renewal in this area suggests that the main principles of neoliberal renewal are an economization of investment, a transition to negotiation-oriented governance, and the individualization of participation.